Is Impression Management Through Status Updates Successful? Meta-Accuracy and Judgment Accuracy of Big Five Personality Traits Based on Status Updates From Social Network Sites in China - Wu, Ting; Zheng, Yong (Frontiers in Psychology, 2019)
Status updates on social network sites (SNSs) as a new medium for people to express “what is on your mind” on the Internet can provide much information. In the current study, we statistically analysed survey data to examine whether individuals utilize impression management in their status updates on SNSs, whether their attempts at impression management are successful, and whether users who post these status updates can infer how others view them based on these contents, whether the status updates posted on SNSs reflect information about users’ Big Five personality traits. The findings suggested that the meta–perception and perceivers’ judgments of all five traits are quite accurate, despite users’ aim to create different impression of most traits in their status updates. This study offers new empirical evidence about the model of interpersonal perception on SNSs and shows that status updates on SNSs can provide considerable information about their authors.